Comparison of the diagnostic accuracy of dynamic and static preload indexes to predict fluid responsiveness in mechanically ventilated, isoflurane anesthetized dogs. (May 2019) - Celeita-Rodríguez, Nathalia; Teixeira-Neto, Francisco J.; Garofalo, Natache A.; Dalmagro, Tábata L.; Girotto, Carolina H.; Oliveira, Guillermo C.V.; Santos, Ivan FC.
Abstract: Objective: To compare the diagnostic accuracy of pulse pressure variation (PPV), stroke volume variation from pulse contour analysis (SVVPCA ), plethysmographic variability index (PVI), central venous pressure (CVP) and global end-diastolic volume index measured by transpulmonary thermodilution (GEDVITPTD ) to predict fluid responsiveness (FR) in dogs. Study design: Prospective study. Animals: A group of 40 bitches (13.8–26.8 kg) undergoing ovariohysterectomy. Methods: Anesthesia was maintained with isoflurane under volume-controlled ventilation (tidal volume 12 mL kg –1 ; inspiratory pause during 40% of inspiratory time; inspiration:expiration ratio 1:1.5). Transpulmonary thermodilution cardiac output was recorded through a femoral artery catheter. FR was evaluated by a fluid challenge (lactated Ringer's, 20 mL kg –1 over 15 minutes) administered once ( n  = 21) or twice ( n  = 18) before surgery. Individuals were responders if stroke volume index measured by transpulmonary thermodilution increased >15% after the last fluid challenge. Results: Of the 39 animals studied, 21 were responders and 18 were nonresponders. Area under the receiver operating characteristics curve (AUROC) was 0.976, 0.906, 0.868 and 0.821 for PPV, PVI, CVP and SVVPCA, respectively ( p < 0.0001 from AUROC = 0.5). GEDVITPTD failed to predict FR (AUROC: 0.660, p  = 0.078). Best cut-off thresholds discriminating responders and nonresponders, with respective zones of diagnostic uncertainty (gray zones) were: PPV >16% (15–16%), PVI >11% (10–13%), SVVPCA >10% (9–18%) and CVP ≤1 mmHg (0–3 mmHg). Percentage of animals within gray zone limits was 13% (PPV), 28% (PVI), 51% (SVVPCA ) and 67% (CVP). Conclusions and clinical relevance: PPV has better diagnostic accuracy to predict FR (conclusive results in nearly 90% of population) than other preload indexes in healthy dogs. When invasive blood pressure is unavailable, PVI will predict FR with reasonable accuracy (conclusive results in approximately 70% of the population). PPV and PVI values above gray zone limits (>16% and >13%, respectively) can reliably predict responders to volume expansion.